Otogenic Lateral Sinus Thrombosis: Case Series and Controversies. (23rd August 2013) - Funamura, Jamie L.; Nguyen, Alexander T.; Diaz, Rodney C.
Abstract : Objectives: 1) Present a series of patients with an increasingly rare but significant complication of otitis media primarily affecting the pediatric population. 2) Review diagnostic and management algorithms for otogenic lateral sinus thrombosis. 3) Discuss controversies in medical and surgical management of lateral sinus thrombosis. Methods: Retrospective chart review of patients treated for otogenic lateral sinus thrombosis at a tertiary care institution from June 1996 through July 2012. Results: Over a 16‐year period, 6 patients were treated at our institution for otogenic lateral sinus thrombosis. Symptoms at presentation included fever, persistent nausea and vomiting, headache, seizure, and facial nerve palsy; duration of symptoms prior to diagnosis varied from 4 days to 3 weeks. Four patients were diagnosed with associated intracranial complications, and 1 was found to have a cholesteatoma. All 6 patients underwent a primary surgery by an otolaryngologist; 1 required a subsequent internal jugular vein ligation, and another required neurosurgical procedures for drainage of intracranial abscesses. Four of 6 patients were anticoagulated, and 1 developed significant anticoagulation‐related complication. Conclusions: Although rarely encountered today, lateral sinus thrombosis remains a serious intracranial complication requiring both medical and surgical intervention with a multidisciplinary effort. Controversies exist as to the degree of surgical intervention and whether anticoagulation is necessary for treatment.